2005
DOI: 10.1007/s10803-005-0010-0
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Autism in Individuals with Down Syndrome

Abstract: As an off-shoot of a study examining the reliability and validity of an adapted version of the Pre-Linguistic Autism Diagnostic Observation Schedule (A-PL-ADOS), 13 individuals with Down syndrome with IQs ranging between 24 and 48 were administered the Autism Diagnostic Interview-Revised (ADI-R) and the A-PL-ADOS, which are well-validated interview and observational diagnostic measures. Three out of 13 met lifetime criteria on the ADI-R, but none of these three showed behavior that met the criterion for autism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 38 publications
(30 reference statements)
2
29
1
5
Order By: Relevance
“…Other factors that may also be contributing to the perceived increase in prevalence include the recent identification of children with genetic disorders unrelated to ASDs who also sometimes can meet criteria for an ASD, such as Down syndrome 58,59 and CHARGE (coloboma, heart disease, choanal atresia, retarded growth and development and/or central nervous system anomalies, genital anomalies and/or hypogonadism, and ear anomalies and/or deafness) syndrome. 60 Finally, diagnosis of an ASD may be made in an older family member with milder symptoms that were previously unrecognized until after the diagnosis of a younger child.…”
Section: Table 2 Diagnostic Criteria For 29980: Asperger's Disorder mentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors that may also be contributing to the perceived increase in prevalence include the recent identification of children with genetic disorders unrelated to ASDs who also sometimes can meet criteria for an ASD, such as Down syndrome 58,59 and CHARGE (coloboma, heart disease, choanal atresia, retarded growth and development and/or central nervous system anomalies, genital anomalies and/or hypogonadism, and ear anomalies and/or deafness) syndrome. 60 Finally, diagnosis of an ASD may be made in an older family member with milder symptoms that were previously unrecognized until after the diagnosis of a younger child.…”
Section: Table 2 Diagnostic Criteria For 29980: Asperger's Disorder mentioning
confidence: 99%
“…Conversely, a few children with genetic syndromes that are characterized by features quite different from ASDs also may meet DSM-IV-TR criteria. For example, recent studies have reported that 6% to 7% of children with Down syndrome (typically characterized by relatively good social skills compared with those in other domains) 59 and almost 50% of children with CHARGE syndrome (associated with mutations of the CHD7 gene 132 ) meet criteria for one of the ASDs. 60 There have also been a few isolated reports of a mitochondrial and/or metabolic abnormality (eg, carnitine deficiency) being associated with an ASD, but the significance of these reports is not clear.…”
Section: Table 2 Diagnostic Criteria For 29980: Asperger's Disorder mentioning
confidence: 99%
“…Embora existam poucas informações sobre o autismo em sujeitos com síndrome de Down, um nú-mero crescente de pesquisas internacionais tem sugerido que esta associação pode ser mais comum do que geralmente se pensava (Castillo et al, 2008;Kent et al, 1998;Starr et al, 2005). Para Subirachs (2005), de 5 a 9% das crianças com síndrome de Down podem apresentar o autismo associado.…”
Section: Comportamentos Autísticos Na Síndrome De Down E Interação Counclassified
“…Para Subirachs (2005), de 5 a 9% das crianças com síndrome de Down podem apresentar o autismo associado. Em uma pesquisa realizada com 13 indivíduos com síndrome de Down, com média de idade de 14 anos e 6 meses, 5 deles apresentaram autismo, e destes somente 1 apresentou habilidade verbal (Starr et al, 2005). Em outro estudo, foram relatados 3 casos de sujeitos com síndrome de Down com diagnóstico de autismo realizado de acordo com o CID-10 ( Kent et al, 1998).…”
Section: Comportamentos Autísticos Na Síndrome De Down E Interação Counclassified
See 1 more Smart Citation